Improved mechanical properties of Mg matrix composites reinforced with Al and carbon nanotubes fabricated by spark plasma sintering followed by hot extrusion. Issue 23 (14th December 2016) - Yan, Yan; Zhang, Hua; Fan, Jianfeng; Wang, Lifei; Zhang, Qiang; Hou, Minjian; Dong, Hongbiao; Xu, Bingshe
Abstract: Abstract : The new processing method of spark plasma sintering (SPS) followed by hot extrusion was developed to produce Mg–1Al– x CNTs composites. Microstructural characterization revealed that the reinforcement particles were distributed uniformly in Mg matrix. The results of mechanical properties indicated a fact that compared with monolithic Mg, all Mg–1Al– x CNTs composites, especially the Mg–1Al–0.15CNTs composite, fabricated by SPS followed by hot extrusion exhibited better tensile and compressive properties. Under tension, Mg–1Al–0.15CNTs composite exhibited higher 0.2% tensile yield strength (TYS) (157 MPa versus 98 MPa, increased by ∼60%) and ultimate tensile strength (271 MPa versus 188 MPa, increased by ∼44%) than monolithic Mg. In compression, Mg–1Al–0.15CNTs composite also obtained a great enhancement in 0.2% compressive yield strength (118 MPa versus 81 MPa, increased by ∼46%) and ultimate compressive strength (321 MPa versus 255 MPa, increased by ∼26%) compared to monolithic Mg. Meanwhile, Mg–1Al–0.15CNTs composite maintained a high tensile failure strain of ∼8.8% and a high compressive failure strain of ∼17.9%.